Strain differentiation of Trichophyton rubrum by randomly amplified polymorphic DNA and analysis of rDNA nontranscribed spacer - Baeza, L. C.; Matsumoto, M. T.; Almeida, Ana Marisa Fusco [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (Soc General Microbiology, 2006)
Trichophyton rubrum is the most common pathogen causing dermatophytosis. Molecular strain-typing methods have recently been developed to tackle epidemiological questions and the problem of relapse following treatment. A total of 67 strains of T rubrum were screened for genetic variation by randomly amplified polymorphic DNA (RAPD) analysis, with two primers, 5'-d[GGTGCGGGAA]-3' and 5'-d[CCCGTCAGCA]-3', as well as by subrepeat element analysis of the nontranscribed spacer of rDNA, using the repetitive subelements TRS-1 and TRS-2. A total of 12 individual patterns were recognized with the first primer and 11 with the second. Phylogenetic analysis of the RAPID products showed a high degree of similarity (> 90 %) among the epidemiologically related clinical isolates, while the other strains possessed 60% similarity. Specific amplification of TRS-1 produced three strain-characteristic banding patterns (PCR types); simple patterns representing one copy of TRS-1 and two copies of TRS-2 accounted for around 85 % of all isolates. It is concluded that molecular analysis has important implications for epidemiological studies, and RAPID analysis is especially suitable for molecular typing in T. rubrum.